Matching expectations: how issue congruence drives satisfaction with democracy - Aurelia Zucaro (QOE-IJES)
This study investigates how issue congruence between citizens and political parties affects satisfaction with democracy (SWD) in France, Germany and Italy. Using data from the 2019 European Election Study and the Chapel Hill Expert Survey, the analysis focuses on three key policy domains, economy, immigration and the environment, and tests whether higher positional alignment within party–citizen dyads is associated with greater democratic satisfaction. Findings from ordered logistic regression (OLR) models show that issue congruence is positively associated with SWD, particularly on identity-related and transnational issues such as immigration and the environment. The study also introduces an original salience index which combines party-level issue emphasis with citizens’ media exposure to examine whether issue salience moderates this relationship. Results indicate that, when an issue is highly salient, the positive effect of congruence weakens, suggesting that heightened attention may raise citizens' expectations and make representational gaps more visible. These findings highlight the contextual and issue-specific dynamics underlying democratic satisfaction in European multiparty systems.